The Model of Virgil and the Rhetoric of “Exordium”: Questions About the Epic Prooemium in the 16th Century Treatises (AOQU (Achilles Orlando Quixote Ulysses). Journal on Epic, 2023)
The essay investigates the 16th century reception of the incipit of the Aeneid as a model for the opening of the epic poem. I focus in particular on the treatment of the four lines («Ille ego qui quondam...») which would originally have been the first part of a larger proemio according to Donato and Servius and would have been removed by the editors of the poem. The lines circulate in many 16th century editions, even with the support of specific exegetical notes, and in the second half of the century they appear in poetics and other vulgar treatises (by Castelvetro, Speroni, Tasso) with the function of exemplifying the precepts relating to the proemio, such as the rhetorical doctrine of the exordium and the prescriptions for the epic opening from Horace’s Ars poetica. The purpose of the essay is to highlight which findings from the exegetical tradition are taken up in the treatises, in the attempt to verify whether and to what extent the spurious opening could represent, at least theoretically, an alternative model to the canonical «Arma virumque cano».
Keywords: Aeneis; 16th century reception of Virgil; Proemio; Rhetoric; Poetics